TAREKAT KHALAWATIAH SAMMAN (Studi tentang Penyebaran dan Ajarannya di Masyarakat Masamba Kabupaten Luwu Utara Sulawesi Selatan) - Nurlidiawati, Nurlidiawati (RIHLAH, 2013)
Mystical path avoiding what is prohibited and what it can lead to sin, It noticed what is possible and what is not, it is also doing what is useful to do and what is sinful when done. The ability of a person is under the guidance of a leader (sheikh) with a specific purpose. "Khalawatiah" is one of the mystical path. Khalwatiah means isolating yourself in a place away from the noise in order to purify themselves from sin to get guidance from God Almighty. According to followers of Khalawatiah Samman, spiritual life is religious heritage started by the Prophet and his companions until now. According to them, Khalwatiah Samman is not contrary to the teachings of Islam, although there are many challenges from all sides. The purpose of this mystical path is to keep his followers in times of peace and quiet under the guidance of teachers. Those involved in the activities of this mystical spiritual undergo regular training, so that they achieve a feeling as to the psychological world, and this is a practical guide for someone who follows the teaching of tasawwuf.